2023
DOI: 10.3390/app13095516
|View full text |Cite
|
Sign up to set email alerts
|

Guided Access through Ceramic Crowns with Fiberglass Post Removal in Lower Molars: An In Vitro Study

Abstract: This in vitro study evaluated the accuracy of guided endodontics for the removal of intraradicular fiberglass posts from posterior mandibular teeth and the influence of the operator’s experience in this procedure. Forty root-filled mandibular first molars with an intraradicular fiberglass post were mounted onto 20 mandibular models. Guides for access were made following surface scanning and cone-beam computed tomography (CBCT) using CoDiagnostix software. The models were randomly divided between two operators … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 29 publications
1
7
0
Order By: Relevance
“…Findings from this review showed that the use of guided endodontics is effective in the removal of dental posts with a low risk of iatrogenic errors. Complications were reported only in the two in vitro studies [29], [30]. Of those, the first one showed an 87.5% success rate and the second one 97.5%.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Findings from this review showed that the use of guided endodontics is effective in the removal of dental posts with a low risk of iatrogenic errors. Complications were reported only in the two in vitro studies [29], [30]. Of those, the first one showed an 87.5% success rate and the second one 97.5%.…”
Section: Discussionmentioning
confidence: 99%
“…The effectiveness was measured by the reviewers as the ability to remove the dental post without causing severe complications such as a fracture or a perforation of the root. In all case reports the post was successfully removed with no complications (100% success rate) [22]- [28] In one in vitro study the post was removed from all but one tooth (97.5% success rate) where perforation occurred [29]. In the other in vitro study, the post was removed in 87.5% of the teeth, in one case it was unsuccessful because the drill bit hit the canal wall [30].…”
Section: Effectiveness and Complicationsmentioning
confidence: 95%
See 2 more Smart Citations
“…In addition, guided endodontics allows minimally invasive access to the apices during endodontic surgery [ 17 19 ]. A few case reports have shown that guided endodontics can be used to successfully remove fiber posts from root-filled teeth [ 20 26 ]. The accuracy of GE to provide access for the removal of intraradicular fiber posts was evaluated in an in vitro study of 40 teeth restored with fiber posts and composite cores, which showed that GE resulted in a mean apical deviation of 0.40 ± 0.19 mm [ 27 ].…”
Section: Introductionmentioning
confidence: 99%